2018
DOI: 10.1007/s00163-018-0301-z
|View full text |Cite
|
Sign up to set email alerts
|

Iterations as the result of social and technical factors: empirical evidence from a large-scale design project

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 75 publications
2
22
0
Order By: Relevance
“…The findings on dynamic robustness, instead, suggest that modular product architectures receive fewer iterations or changes and are robust to their propagation. This is congruent with empirical research that has shown that modularity is associated with a decrease in the number of errors, changes, and iterations (MacCormack et al, 2006;Piccolo et al, 2019;Sosa et al, 2013). With respect to a process architecture, our research suggests that modularity can add stability to a process and can help to confine iterations inside process modules, thus avoiding catastrophic cascades.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The findings on dynamic robustness, instead, suggest that modular product architectures receive fewer iterations or changes and are robust to their propagation. This is congruent with empirical research that has shown that modularity is associated with a decrease in the number of errors, changes, and iterations (MacCormack et al, 2006;Piccolo et al, 2019;Sosa et al, 2013). With respect to a process architecture, our research suggests that modularity can add stability to a process and can help to confine iterations inside process modules, thus avoiding catastrophic cascades.…”
Section: Discussionsupporting
confidence: 89%
“…Higher modularity can promote higher changeability as an effect of the loose coupling between modules, which makes it possible to substitute or upgrade a module in isolation or with fewer local changes (Hölttä and Otto, 2005;Thomke, 1997;Ulrich, 1995;Worren et al, 2002). As changes, errors, and perturbations can remain localised without being propagated to the whole system, modularity can increase system robustness (Giffin et al, 2009;Pan and Sinha, 2007;Piccolo et al, 2019;Suh et al, 2007). Finally, the presence of loosely coupled or independent modules makes it possible to implement parallelisation (Gershenson et al, 2003;Parraguez et al, 2019;Yassine and Braha, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of different approaches reflects (and is reflected in) the types of insights gained, but also may facilitate triangulation of findings. The papers included in this Special Issue use a range of research approaches, including study of design teams in representative situations (Martinec et al 2019;Gralla et al 2019), study of projects in a university context (Menold et al 2019;Li et al 2019), computer simulation of design and development processes (Zhang and Thomson 2019), industry workforce surveys (De Lessio et al 2019), industry interviews and document analysis (Tahera et al 2019) and retrospective analysis of project data (Piccolo et al 2019).…”
Section: Themesmentioning
confidence: 99%
“…Their research draws on a case study in a large company that develops complex scientific instruments. Thirdly on the meso-level, Piccolo et al (2019) take a socio-technical perspective on iteration in the design and development process. They argue that, while many researchers consider design iteration from either a technical perspective (e.g.…”
Section: Overview Of This Special Issuementioning
confidence: 99%